2003
DOI: 10.1590/s0100-72032003000900002
|View full text |Cite
|
Sign up to set email alerts
|

A influência do estado nutricional da adolescente grávida sobre o tipo de parto e o peso do recém-nascido

Abstract: portantes para os tocoginecologistas e autoridades de saúde, sobretudo em relação ao início precoce da atividade sexual. A maioria dos adolescentes carece de conhecimento adequado sobre saúde sexual e reprodutiva, obtendo as primeiras informações com os próprios colegas, cujas noções podem não ser adequadas, determinando, entre as jovens, repercussões como doenças sexualmente transmíssíveis (DST) e gestações não planejadas¹.Conceitua-se adolescência como a fase da transição entre a infância e a idade adulta, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
10

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 3 publications
0
7
0
10
Order By: Relevance
“…The higher probability of low weight among teenagers results from the several physical, behavioral, psychological and hormonal changes that usually occur in this period, including the tireless quest for slimness 21 . Smoking is considered an independent risk factor for low BMI in adults because it impacts on the appetite and causes the expenditure of money with cigarettes to the detriment of food 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The higher probability of low weight among teenagers results from the several physical, behavioral, psychological and hormonal changes that usually occur in this period, including the tireless quest for slimness 21 . Smoking is considered an independent risk factor for low BMI in adults because it impacts on the appetite and causes the expenditure of money with cigarettes to the detriment of food 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Tal achado é descrito na literatura que demonstra uma importante relação positiva entre o ganho de peso gestacional e o peso ao nascer 8,14,30 . É descrito, ainda, que o ganho de peso no primeiro trimestre de gestação é importante preditor do peso ao nascer e do índice ponderal do recém-nascido 26,31 .…”
Section: Discussionunclassified
“…Furlan at al. reported a prevalence of malnutrition during pregnancy of 27.7% [19] and Rosado observed that 39.1% of pregnant teenagers started pregnancy undernourished [20].…”
mentioning
confidence: 99%